STRATEGY FOR DEVELOPING THE SALULIANG TOURIST OBJECT IN SAWANGAN, MALIMBONG, BALEPE DISTRICT - Abedneigo Carter Rambulangi; Oktavianus Pasoloran; Althon Karaman Pongtuluran; Agustinus Mantong; Yohanis L. Ta’dung; Westerini Lusdani; Prajman.E.Pasambo; Natasya Bua’Langi (ITB AAS Indonesia Surakarta, 2026)
The study aims to determine the Strategy For Developing The Saluliang Tourist Object In Sawangan, Malimbong, Balepe District. This research is qualitative. The informants in this study were the managers of the Saluliang Kolesawangan tourist attraction. Data collection methods used were interviews, observation, and documentation.The data analysis techniques used in this study are data presentation, data reduction and drawing conclusions.The results of this study indicate that the strategy carried out by the Saluliang Tourism Object Manager in developing its tourism sector is by collaborating with the Tana Toraja Regency Tourism Office to hold training, especially in the field of marketing, carrying out promotional and marketing strategies with 2 (two) approaches, namely Offline and Online. Not only that, the local community also plays a role as supervisors, implementers and recipients, besides that the local community also plays a role in developing culinary and woven fabrics to be seen and sold to visitors. Keywords : Development Strategy, Tourism, Saluliang Kolesawangan Tourist Attraction